Water Footprint from Grow ing Potato Crops in Cuba - Cabello, Juan José; Sagastume, Alexis; López Bastida, Eduardo; Vandecasteele, Carlo; Hens, Luc (Tecnología y ciencias del agua, 2016)
This article determines the water footprint from the potato crop in Cuba between the years 2009 and 2012 using the CROPWAT model. Climate, yields and fertilization data are specific to each of the areas where the crops were grown. The results are compared with previous works in other countries in Latin America and the Caribbean. In the case of Cuba, the results show a difference of 25% with respect to international reports developed with data related to climate and average crops in the country. Other countries in the region have similar levels, although with a smaller gray component and a larger green component. The water footprint from potato crops is also compared with other crops in Cuba, finding that potatoes represent the fourth largest water demand